2015
DOI: 10.1055/s-0035-1563669
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Outcomes of Aortic Valve Replacement with Aortic Annular Enlargement: A Propensity Analysis

Abstract: Objectives Early and late outcomes were evaluated in Japanese patients undergoing aortic valve replacement (AVR) with or without aortic annular enlargement (AAE). Propensity matching adjusted for baseline differences in this study. Methods Between January 2001 and July 2014, 589 patients underwent AVR for aortic stenosis. Of these, 58 patients received AVR with AAE (AAE group), and the others received standard AVR without annular enlargement (sAVR group). Of these 589 patients, 116 patients were selected using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The JBI tool for non-randomised studies revealed a moderate risk of bias in 13 studies, 6,10,11,20,21,2326,2831 and a low risk of bias in one study. 27 Further details are mentioned in (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…The JBI tool for non-randomised studies revealed a moderate risk of bias in 13 studies, 6,10,11,20,21,2326,2831 and a low risk of bias in one study. 27 Further details are mentioned in (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…Our study is the first to directly compare the shortterm outcomes of AAE between the established operative techniques, Nicks and Manouguian, and the newlyintroduced Y-incision technique. The Nicks and Manouguian techniques have seen widespread utilization since they were developed in the 1970s, and there have been numerous studies which evaluated their safety profiles in comparison with AVR without annular enlargement (19)(20)(21)(22)(23)(24). By contrast, the Y-incision technique has only been used since August 2020, and has not yet had widespread use.…”
Section: Discussionmentioning
confidence: 99%
“…Title and abstract screening were performed in duplicate, identifying 139 potentially eligible studies that underwent full-text review by two independent reviewers. Overall, 32 potentially eligible studies (12,13,20,21,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) were identified (52)(53)(54)(55)(56)(57)(58)(59)(60), including 17 studies (13,45-60) that were excluded because they did not include any information on at least one of the mid-term outcomes of interest through 5 years of followup. Consequently, 15 unique studies (12,20,21,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) remained and were included in data extraction and quantitative synthesis.…”
Section: Literature Searchmentioning
confidence: 99%
“…All 15 included studies are observational and nonrandomized (12,20,21,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Of the included studies, five compared propensity-matched groups (34,36,38,41,43), two employed case-control designs to define their reference SAVR groups (34,42), and four reported adjusted midterm outcomes of interest (21,37,43,44).…”
Section: Quality Of Evidencementioning
confidence: 99%
See 1 more Smart Citation